Wildfowl conservation in the Netherlands - Matthews, G V T (Wildfowl, 1957)
The Netherlands and the British Isles are so intimately connected in the pattern of wildfowl distribution that some knowledge of conservation measures being undertaken in the former country is necessary for a full understanding of our own situation. I was therefore fortunate to be invited to join a party which Dutch conservationists took on a tour of their reserves in November 1956. The information gathered on this trip was supplemented by observations made on other visits in September 1955 and June 1956.